Implementasi Kurikulum Perguruan Tinggi Khas Pesantren Di Ma’had Aly Al Tarmasi Perguruan Islam Pondok Tremas Pacitan - Eko Wahid B (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study focuses on reviewing and analyzing curriculum development data at the Islamic College of Ma'had Aly Al Tarmasi, Pondok Tremas, Pacitan. The curriculum development process at the Islamic College of Pondok Tremas, Pacitan, is examined in depth, and several ideas for curriculum improvement are discussed. A qualitative approach was used in this study. Primary data were obtained through in-depth interviews with the principal, vice principal, curriculum planner, and instructors. Secondary data also included information on the basic principles or guidelines underlying the curriculum development process at Pondok Tremas, as well as information on contextual factors influencing the curriculum formulation of Ma'had Aly Al Tarmasi. Structured interviews, observations, and thorough documentation were the data collection procedures. Steps such as data reduction, data presentation, and data verification were part of the data analysis, which are usually conducted before the actual research is conducted. The results of the study indicate that the curriculum development concept of Ma'had Aly Al Tarmasi, Islamic College of Pondok Tremas, Pacitan, meets good criteria. Furthermore, because Ma'had Aly has complete freedom to develop, review, and oversee its own curriculum, the curriculum development process follows appropriate standards. The development of the Ma'had Aly curriculum has had a significant impact on students' abilities and encouraged them to reach their maximum potential. Research shows that the Ma'had Aly Al Tarmasi curriculum continues to be improved, making it a model for curriculum development for other Ma'had Aly educational institutions and universities.